Experimental and finite element study of one span concrete bridge bent designed by the requirements of the 1970s, under gravity and lateral load - Mohammad Kazem Bahrani; Amin Nooralizadeh; Mahdy Sharify; Najmeh Karami (Numerical Methods in Civil Engineering)
In recent years, there has been a growing seismic demand for existing bridges and the final redesign of bridges, especially after a major earthquake One method to strengthen concrete frames on bridges is to use steel sheets or profiles to use the confining force. During this study, a sample at 30% scale under gravity and lateral cycle loading was examined within the laboratory. A finite element model is additionally used to compare the behavior of laboratory samples. The laboratory sample was a model of a typical bridge in iran that was generally designed with deficient detailing requirements in agreement with the typical regulations of the 1970s. A finite element analysis set was used to evaluate various parameters in improving the behavior of the laboratory sample. The finite element model correctly predicted the weakness of the model. Subsequently, a reinforced specimen was investigated by increasing the prestressing force within the concrete beam and the thickness of the frp sheets utilized in the bridge pier by the finite element method. The results show the energy absorbed within the hysteresis curves improved the propagation of the failure. The  result also  showed that  a 100% increase in the prestressing load caused a 67% increase in resistance .